PENERAPAN SKS DI MAN 1 MEDAN (Analisis Signifikansinya Dalam Percepatan Belajar Siswa) - Rahmat Rifai Lubis; Shofiah Nurul Huda; Hilman Rizky Hasibuan (STAI Asy-Syukriyyah, 2021)
The SKS in secondary schools is interesting innovation to research. This study aims to determine: 1) the application 2) significance for acceleration, and 3) supporting and inhibiting. This research conducted at MAN 1 Medan. The research method is qualitative with descriptive study model, the results is MAN 1 Medan applies SKS-B type where the principles: 1) gradually, 2) mapping student ability, 3) comprehensive assessment 4) use UKBM, 5) use 2013 Curriculum, 6) the teacher as facilitator, 7) students required take 6 semesters (51 JP /semester) with study period maximum 4 years, 8) provide PA. It’s found that the significance of acceleration student learning is still not visible even though the system allows it, the supporting factors: easy administration of preparation, good teacher response, parental cooperation and adequate facilities. While the obstacles: schools are still adjusting, online learning constraints and they still looking for the best pattern in implementing this SKS.